2009
DOI: 10.1016/j.bbmt.2009.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-Intensity Conditioning followed by Peripheral Blood Stem Cell Transplantation for Adult Patients with High-Risk Acute Lymphoblastic Leukemia

Abstract: Acute lymphoblastic leukemia (ALL) with high-risk features has a poor prognosis in adults despite aggressive chemotherapy. Reduced-intensity conditioning (RIC) is a lower toxicity alternative for high-risk patients requiring hematopoietic cell transplantation (HCT), however it has not been widely used for ALL. We conducted a retrospective study of 24 high-risk adult ALL patients who received an RIC regimen of fludarabine/melphalan prior to allogeneic peripheral blood stem cell transplant between 6/14/02 and 6/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 26 publications
4
47
0
Order By: Relevance
“…[40][41] Only for patients with low disease burden at the time of transplant, either in a CR or with low WBC and % blasts, can OS and DFS at 2 years reach 61.5%. 42 Compared to these studies, the effectiveness of IDA-intensified conditioning regimen in our study achieved better outcome.…”
Section: Discussionmentioning
confidence: 78%
“…[40][41] Only for patients with low disease burden at the time of transplant, either in a CR or with low WBC and % blasts, can OS and DFS at 2 years reach 61.5%. 42 Compared to these studies, the effectiveness of IDA-intensified conditioning regimen in our study achieved better outcome.…”
Section: Discussionmentioning
confidence: 78%
“…In an attempt to avoid the high NRM seen with MAC-SCT and to exploit the GVL effect, investigators have been exploring the role of reduced-intensity conditioning (RIC) regimens for adult ALL patients who are considered poor candidates for MAC-SCT [11][12][13][14][15][16][17]. However, the role of RIC-SCT in adult ALL remains unclear because the interpretation of transplantation outcome is mainly limited by the small number of patients, short follow-up duration, various regimens for conditioning and graft-versus-host disease (GVHD) prophylaxis, and the heterogeneity of the criteria used to select patients for transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, allo-SCT using reducedintensity conditioning (RIC) may provide opportunities to obtain a significant GVL effect, without the adverse effects of intense myeloablative preparative regimens. [14][15][16][17] Marks et al 18 reported no effect of conditioning intensity on TRM or relapse risk after RIC and MAC in 93 and 1428 Ph chromosome-negative ALL patients, respectively, in first or second CR and in patients 416 years of age who received allografts from siblings and unrelated donors. Mohty et al 19 reported no effect of conditioning intensity on leukemiafree survival after RIC and after MAC in 127 and 449 ALL patients, respectively, in first or second CR and in patients 445 years of age who received allografts from HLA-identical sibling donors and were followed up for a median period of 16 months.…”
Section: Introductionmentioning
confidence: 99%